Meta-GWAS identifies the heritability of acute radiation-induced toxicities in head and neck cancer. (November 2022) - Naderi, Elnaz; Schack, Line M.H.; Welsh, Ceilidh; Sim, Adelene Y.L.; Aguado-Barrera, Miguel E.; Dudding, Tom; Summersgil, Holly; Martínez-Calvo, Laura; Ong, Enya H.W.; Odding, Yasmin; Varela-Pazos, Ana; Steenbakkers, Roel J.H.M.; et al.
Graphical abstract: Highlights: Acute radiation-induced toxicities (RITS) are heritable phenotypes and ∼29% of their variances are explained by common genetic variants. Three potential novel mechanisms for RITs are exoribonuclease activity, inositol phosphate-mediated signaling, and drug catabolic process. Using genetic markers is effective to understand the mechanism of acute RITs, and to predict acute RITs by employing polygenic risk scores. Genetically enriched prediction model for RITs followed by radiation-dose adjustment contributes to attaining personalized radiotherapy. Abstract: Background and purpose: We aimed to the genetic components and susceptibility variants associated with acute radiation-induced toxicities (RITs) in patients with head and neck cancer (HNC). Materials and methods: We performed the largest meta-GWAS of seven European cohorts (n = 4, 042). Patients were scored weekly during radiotherapy for acute RITs including dysphagia, mucositis, and xerostomia. We analyzed the effect of variants on the average burden (measured as area under curve, AUC) per each RIT, and standardized total average acute toxicity (STATacute ) score using a multivariate linear regression. We tested suggestive variants (p < 1.0x10 -5 ) in discovery set (three cohorts; n = 2, 640) in a replication set (four cohorts; n = 1, 402). We meta-analysed all cohorts to calculate RITs specific SNP-based heritability, and effect of polygenic risk scores (PRSs), and genetic correlations among RITS. Results: From 393 suggestive SNPs identified in discovery set; 37 were nominally significant (preplication  < 0.05) in replication set, but none reached genome-wide significance (pcombined  < 5 × 10 -8 ). In-silico functional analyses identified "3′-5'-exoribonuclease activity" (FDR = 1.6e-10) for dysphagia, "inositol phosphate-mediated signalling" for mucositis (FDR = 2.20e-09), and "drug catabolic process" for STATacute (FDR = 3.57e-12) as the most enriched pathways by the RIT specific suggestive genes. The SNP-based heritability (±standard error) was 29 ± 0.08 % for dysphagia, 9 ± 0.12 % (mucositis) and 27 ± 0.09 % (STATacute ). Positive genetic correlation was rg = 0.65 (p = 0.048) between dysphagia and STATacute . PRSs explained limited variation of dysphagia (3 %), mucositis (2.5 %), and STATacute (0.4 %). Conclusion: In HNC patients, acute RITs are modestly heritable, sharing 10 % genetic susceptibility, when PRS explains < 3 % of their variance. We identified numerus suggestive SNPs, which remain to be replicated in larger studies.